Sol–gel‑templated bioactive glass scaffold: a review - Shoushtari, Maryam Sarmast; Hoey, David; Awang Biak, Dayang Radiah; Abdullah, Norhafizah; Kamarudin, Suryani; Zainuddin, Halimatun S. (Springer Science and Business Media Deutschland GmbH, 2024)
Purpose This review paper explores diverse synthesis strategies within the sol–gel technique for producing silicate bioglass with a focus on tailoring these materials for bone scaffold design. Method A comprehensive search was conducted across various databases, including ScienceDirect, Taylor & Francis, Pub- Med, Hindawi, Royal Society of Chemistry (RSC), Wiley Online Library, ResearchGate, and Google Scholar, using keywords such as “silica bioglass,” “Sol–gel technique,” “Templating,” and “Bone scaffold.” The analysis considered variables such as the sol–gel method, the templating approach, and materials used to fabricate silica bioglass bone scaffolds. Out of 140 initially identified studies, 92 were selected for detailed review published within the last two decades. Result and conclusion In this study, the effect of the sol–gel fabrication technique on the improvement of the structure of silicate bioglass bone scaffolds has been reviewed, along with a consideration of the associated advantages and disadvantages. Specifically, the focus of this study was on the templating sol–gel method and its direct impact on morphology and pore structures. Consequently, these findings have evaluated the development of templating sol–gel fabrication techniques for enhancing the bioactivity and biocompatibility of bone scaffolds.